Selenization effects on photovoltaic properties of spray pyrolyzed CuInS2, and CuInS2/In2S3 bi-layer - Woon, Mark Tian Cheng. (2012)
Current methods for fabricating a CuInSxSe2-x solar cell have proven costly and sometimes require toxic chemicals and methods such as KCN etching and H2Se selenization. Spray pyrolysis has been deemed as one of the cheapest and easiest method of fabricating a solar cell, but is limited by small grain sizes which limit efficiency. Presented is a method of obtaining large grains via spray pyrolysis of a CuInS2/In2S3 bi-layer and selenization using Se vapour, while showing the effects on photovoltaic parameters of a solar cell.